2007
DOI: 10.1111/j.1365-313x.2007.03274.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial‐ and plant‐type phosphoenolpyruvate carboxylase polypeptides interact in the hetero‐oligomeric Class‐2 PEPC complex of developing castor oil seeds

Abstract: SummaryTwo classes of phosphoenolpyruvate carboxylase (PEPC) sharing the same 107-kDa catalytic subunit (p107) were previously purified from developing castor oil seed (COS) endosperm. The association of p107 with an immunologically unrelated 64-kDa polypeptide (p64) causes pronounced physical and kinetic differences between the Class-1 PEPC p107 homotetramer and Class-2 PEPC p107/p64 hetero-octamer. Tryptic peptide sequencing matched p64 to the deduced C-terminal half of several bacterial-type PEPCs (BTPCs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
158
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(171 citation statements)
references
References 26 publications
10
158
0
Order By: Relevance
“…Peptide mass fingerprinting also confirmed that the copurifying p93 is SUS (Supplemental Table S3). Extensive copurification of developing COS Class-1 PEPC with SUS also occurs (Gennidakis et al, 2007). Future research is needed to assess the intriguing possibility that these two key enzymes of cytosolic carbohydrate metabolism might physically interact in vivo.…”
Section: Pepc Purification and Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptide mass fingerprinting also confirmed that the copurifying p93 is SUS (Supplemental Table S3). Extensive copurification of developing COS Class-1 PEPC with SUS also occurs (Gennidakis et al, 2007). Future research is needed to assess the intriguing possibility that these two key enzymes of cytosolic carbohydrate metabolism might physically interact in vivo.…”
Section: Pepc Purification and Msmentioning
confidence: 99%
“…The deduced sequence contains: (1) the C-terminal QNTG tetrapeptide characteristic of PTPCs, (2) exact matches to MS/MS derived sequences determined for all four tryptic peptides obtained from the p110 and p107 subunits of the PEPC purified from stage I and II proteoid roots (Fig. 5C), and (3) Ser and Lys residues that align with the positions of the phosphorylatedSer-11 and monoubiquitinated-Lys-628 of developing and germinating COS PTPC (RcPPC3), respectively, and that appear to be absolutely conserved in all PTPCs (Tripodi et al, 2005;Gennidakis et al, 2007;Uhrig et al, 2008;O'Leary et al, 2011a). Research is in progress to isolate a full-length PTPC complementary DNA from proteoid roots of -Pi harsh hakea to determine if its deduced amino acid sequence matches that derived by sequencing the transcriptome of nonproteoid roots.…”
Section: Pepc Purification and Msmentioning
confidence: 99%
See 1 more Smart Citation
“…All immunoblot results were replicated a minimum of three times, with representative results shown in the various figures. Nondenaturing PAGE was carried out using 7% separating gels (Gennidakis et al, 2007). In-gel APase activity staining was performed by equilibrating the gels in 100 mM Na acetate (pH 5.6) containing 10 mM MgCl 2 for 30 min, and then incubating in equilibration buffer containing 1 mg mL 21 Fast Garnet GBC and 0.03% (w/v) b-naphthyl-P.…”
Section: Protein Electrophoresis and Immunoblottingmentioning
confidence: 99%
“…Normalization of RNA for RT was performed for each sample by density measurement of 28S ribosomal RNA bands from the above gel (scanned using ImageJ software from the National Institutes for Health). RNA (5 mg) was reverse transcribed with Superscript III (Invitrogen) and noncompetitive RT-PCR was performed as described in Gennidakis et al (2007). Primers used to amplify AtPPCK1, AtPAP17, AtPAP26, and AtACT2 were previously described (Veljanovski et al, 2006;Gregory et al, 2009).…”
Section: Rna Isolation and Semiquantitative Rt-pcrmentioning
confidence: 99%